Analysis of Website and Marketing Promotion To Facilitate Online Marketing in Printing Retail Industry - Patankar, Ashutosh (2011)
In today’s era of internet with evolution of Web 2.0, all the organisations dealing in retail are going online. In fact online presence has been mandatory requirement today and does no longer hold any competitive advantage by far. In country like India, printing retail industry has been found to be in a state of growth. There is wide array of literature available that analyzes critical success factors for online marketing in general as well as precisely for retail industry. This management project aimed to explore in detail how factors like website & marketing promotion facilitate online marketing in Printing Retail Industry in India. Case study of firm named “Printo Document Services Pvt. Ltd.” located in Bangalore city of India was used for research in this project.